Applying Of Jigsaw Model To Enhance Students’ Reading Comprehension - Sudirman, Sudirman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The purpose of the research was to know the Jigsaw learning model can enhance on VII grade students’ cognitive learning outcomes in reading comprehension at SMPN 1 Praya Barat. It was participant classroom action research. It was done in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. Subject of the research was 32 students. Instruments used were students' test, students' and teacher’s activities used observation sheets, at the end of each cycle. The research findings show that implementation of Jigsaw learning model can improve students' cognitive competence. Percentage of students' classical achievement in cognitive competence improves time by time. In pre-cycle, the percentage is 46% (not enough), in cycle I is 50% (not enough) and in cycle II is 92% (very good). Meanwhile, percentage of students' Activity also improves. In pre-cycle, the percentage is 52% (enough), in cycle I is 64% (good) and in cycle II  is 80% (very good).  From the finding, it proves that the implementation of Jigsaw learning model can improve students' cognitive competence and Activity in class VII of SMPN 1 Praya Barat